Programmable C‐to‐U RNA editing using the human APOBEC3A deaminase. (15th October 2020) - Huang, Xinxin; Lv, Junjun; Li, Yongqin; Mao, Shaoshuai; Li, Zhifang; Jing, Zhengyu; Sun, Yidi; Zhang, Xiaoming; Shen, Shengxi; Wang, Xinxin; Di, Minghui; Ge, Jianyang; et al.
Abstract: Programmable RNA cytidine deamination has recently been achieved using a bifunctional editor (RESCUE‐S) capable of deaminating both adenine and cysteine. Here, we report the development of "CURE", the first cytidine‐specific C‐to‐U RNA Editor. CURE comprises the cytidine deaminase enzyme APOBEC3A fused to dCas13 and acts in conjunction with unconventional guide RNAs (gRNAs) designed to induce loops at the target sites. Importantly, CURE does not deaminate adenosine, enabling the high‐specificity versions of CURE to create fewer missense mutations than RESCUE‐S at the off‐targets transcriptome‐wide. The two editing approaches exhibit overlapping editing motif preferences, with CURE and RESCUE‐S being uniquely able to edit UCC and AC motifs, respectively, while they outperform each other at different subsets of the UC targets. Finally, a nuclear‐localized version of CURE, but not that of RESCUE‐S, can efficiently edit nuclear RNAs. Thus, CURE and RESCUE are distinct in design and complementary in utility. Synopsis: The current approach for programmable C‐to‐U RNA editing (RESCUE‐S) is limited by low editing efficiency at certain targets, the inability to edit nuclear RNAs, and non‐specific deamination of adenosines. Here, an alternative C‐to‐U RNA editing system—"CURE"—is introduced that complements RESCUE‐S in application. Fusion of the human cytidine‐specific deaminase APOBEC3A to dCas13 yields a distinct C>U RNA editor (CURE) The CURE system uses unconventional guide RNAs, which induce loops at target sites to imitate the natural substrate of APOBEC3A CURE and RESCUE‐S can complement each other in terms of editing motif preference, on‐target editing efficiency and off‐target effects. Abstract : A new tool—the "CURE" base editor—based on an APOBEC3A‐dCas13 fusion functioning with unconventional gRNAs increases efficiency and reduces off‐target substitutions in C‐to‐U RNA editing.